Capturing User Requirements in Medical Device Development: The Role of Ergonomics - Martin, Jennifer L.; Murphy, Elizabeth; Crowe, John A.; Norris, Beverley J. (Institute of Physics, 2006)
Measuring and fulfilling user requirements during medical device development will result in successful products that improve patient safety, improve device effectiveness and reduce product recalls and modifications. Medical device users are an extremely heterogeneous group and for any one device the users may include patients, their carers as well as various healthcare professionals. There are a number of factors that make capturing user requirements for medical device development challenging including the ethical and research governance involved with studying users as well as the inevitable time and financial constraints. Most ergonomics research methods have been developed in response to such practical constraints and a number of these have potential for medical device development. Some are suitable for specific points in the device cycle such as contextual inquiry and ethnography, others, such as usability tests and focus groups may be used throughout development. When designing user research there are a number of factors that may affect the quality of data collected including the sample of users studied, the use of proxies instead of real end-users and the context in which the research is performed. As different methods are effective in identifying different types of data, ideally more than one method should be used at each point in development, however financial and time factors may often constrain this.